The Orthodox Reality: Culture, Theology, and Ethics in the Modern World, by Vigen Guroian - Neel, Caleb (The Evangelical quarterly, 2021)
"The Orthodox Reality: Culture, Theology, and Ethics in the Modern World, by Vigen Guroian" published on 09 Nov 2021 by Brill.